A prospective study of peer victimization and depressive symptoms among left-behind children in rural China: the mediating effect of stressful life events - Xiaoqing Zhang; Houlin Hong; Wei Hou; Xia Liu (BMC, 2022)
Abstract Background The Ministry of Civil Affairs of the People's Republic of China reported that in 2018, 6.97 million left-behind children (LBC), children who live in rural areas away from their parents, were being cared for by grandparents, relatives, elder siblings, or often living alone. Their parents have migrated to cities for better income opportunities. While a number of studies have detailed elevated depressive symptoms among LBC, relatively little is known about the causes of poorer mental health in LBC. Methods This study used longitudinal data to examine associations between peer victimization, stressful life events, and depressive symptom severity in LBC from four randomly-selected middle schools in Guizhou Province, China. A total of 862 children aged 11-18 years, with 472 LBC (54.76%) and 390 non-left-behind children (NLBC) (45.24%), were included in the analysis. T-test was used to compare the depressive symptoms, peer victimization, and stressful life events between LBC and NLBC at baseline and follow-up (6 months later). Multivariable linear regression models were used to examine the mediation effect of follow-up stressful life events on the relationship between baseline peer victimization and follow-up depressive symptoms among LBC. Results Results suggested that LBC had higher peer victimization and stressful life events than NLBC (β = 1.28, p = 0.04), and peer victimization and stressful life events at baseline were associated with increased follow-up depressive symptoms among LBC (Peer victimization: β = 0.25, p < 0.0001; Stressful life events: β = 0.15, p < 0.001). Peer victimization affected depressive symptoms partially through stressful life events for female LBC and completely through stressful life events for male LBC, controlling for age, perceived socioeconomic status, and school. Conclusions This study highlights the vulnerability of LBC exhibiting negative mental health outcomes as they were found to experience more peer victimization and feel more stressed when stressful life events happened, compared with NLBC. Results of this study suggested that protecting LBC from peer victimization experiences can potentially prevent LBC from experiencing an increased impact of other stressful life events, thus decreasing the likelihood of their depressive symptoms. Intervention design should consider the different mediating effects of stressful life events on the relationship between peer victimization and depressive symptoms among female and male LBC.